2015
DOI: 10.1016/j.jse.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison between the trapezius transfer and latissimus transfer for irreparable posterosuperior rotator cuff tears

Abstract: The lower trapezius transfer is superior to the latissimus transfer at restoring native glenohumeral kinematics and joint reaction forces in our cadaveric model. It may be a promising treatment option for patients with a massive irreparable rotator cuff tear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 25 publications
3
75
0
4
Order By: Relevance
“…32 Although reverse total shoulder arthroplasty is a viable salvage procedure, implant longevity and failure preclude the use of arthroplasty in this young and active population. 33 Whereas latissimus dorsi tendon transfer is thought to restore external rotation and re-establish the anterior-posterior force couples on the humeral head, the orientation of the tenodesis places a nonphysiological vector across the shoulder joint. 33 This may be a reason for the high progression of osteoarthritis that has been described after the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Although reverse total shoulder arthroplasty is a viable salvage procedure, implant longevity and failure preclude the use of arthroplasty in this young and active population. 33 Whereas latissimus dorsi tendon transfer is thought to restore external rotation and re-establish the anterior-posterior force couples on the humeral head, the orientation of the tenodesis places a nonphysiological vector across the shoulder joint. 33 This may be a reason for the high progression of osteoarthritis that has been described after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…33 Whereas latissimus dorsi tendon transfer is thought to restore external rotation and re-establish the anterior-posterior force couples on the humeral head, the orientation of the tenodesis places a nonphysiological vector across the shoulder joint. 33 This may be a reason for the high progression of osteoarthritis that has been described after the procedure. 13,34 Elhassan et al 35 described the use of a lower trapezius tendon transfer with an Achilles allograft augmentation in patients with irreparable rotator cuff tears.…”
Section: Discussionmentioning
confidence: 99%
“…A biomechanical study by Omid et al [40] compared the latissimus transfer to the trapezius transfer in 0, 30, and 60 degrees of abduction. The authors concluded that the trapezius transfer is superior to latissimus transfer in restoring glenohumeral kinematics and force couples [41].…”
Section: Trapezius Transfermentioning
confidence: 99%
“…4 (A-D) Transferência do tendão do grande dorsal (TGD) alongado e reforçado com um enxerto tendinoso homólogo realizada por uma abordagem deltopeitoral isolada, conforme descrito por Miyazaki et al 61 foi demonstrado que as forças de tensão e excursão do trapézio são muito semelhantes às do infraespinal. 38,39 Em um estudo com cadáveres, Omid et al 39 73 a única diferença foi o uso de um enxerto autólogo de tendão semitendíneo em vez de um enxerto homólogo de tendão calcâneo. Os autores avaliaram 14 pacientes por um período médio de 24 meses (faixa de 12 a 36 meses).…”
Section: Transferência Do Tendão Do Trapézio Inferior (Tti)unclassified